Efficient electrochemical detection of pancreatic cancer marker CA19-9 using biosynthesized gold nanoparticles from mint extract for electrode modification - Xiaohui Wang; Yu Liu; Bude Su; Jinhua Tan; Jianxin Shen; Qi Chen; Yu Gou; Ying Zhang (Alexandria Engineering Journal, 2025)
This study presents a novel electrochemical biosensor for the detection of CA19–9, a crucial pancreatic cancer biomarker, utilizing gold nanoparticles (AuNPs) biosynthesized from mint extract. The green synthesis approach yielded well-dispersed, spherical AuNPs with a characteristic surface plasmon resonance peak at 520 nm. Modification of glassy carbon electrodes with these AuNPs resulted in a significant enhancement of electrochemical properties, including a 50 % increase in peak current and a 66.7 % reduction in charge transfer resistance. The biosensor exhibited a wide linear range from 0.1 to 100 U/mL with excellent linearity (R² = 0.998) and achieved a remarkably low limit of detection of 0.05 U/mL. The sensor demonstrated high specificity against common interfering substances and maintained stability over 100 cycles with less than 5 % decrease in performance. Compared to traditional ELISA methods, this biosensor offers rapid detection, minimal sample preparation, and superior sensitivity. The integration of biosynthesized AuNPs not only enhanced the sensor's performance but also aligned with sustainable practices in nanomaterial synthesis. This innovative approach paves the way for the development of sensitive, eco-friendly, and cost-effective diagnostic tools for early pancreatic cancer detection and monitoring.